2016
DOI: 10.1002/anie.201605687
|View full text |Cite
|
Sign up to set email alerts
|

From 0 to II in One‐Electron Steps: A Series of Ruthenium Complexes Supported by TropPPh2

Abstract: We report the synthesis of a series of ruthenium complexes supported by the phosphine olefin ligand tropPPh2 (trop=5-H-dibenzo-[a,d]cyclohepten-5-yl) in the oxidation states 0, +I, and +II, formed via successive one-electron oxidization steps from Ru(0) (tropPPh2 )2 . The bidentate character of the tropPPh2 ligand and its steric hindrance force the complexes to adopt uncommon geometries, which were investigated by X-ray diffraction analysis. EPR data of the mononuclear Ru(I) complex reveal couplings of the unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Recently, the group of Grützmacher reported the remarkable 4‐coordinate 15‐electron complex [Ru I (tropPPh 2 ) 2 ]BF 4 featuring two bidentate tropPPh 2 ligands (trop=5 H ‐dibenzo[ a,d ]cyclohepten‐5‐yl)). Besides Ru I , this ligand scaffold stabilizes ruthenium complexes in oxidation states ranging from Ru 0 to Ru II . No further reactivity with this complex has been reported to date.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the group of Grützmacher reported the remarkable 4‐coordinate 15‐electron complex [Ru I (tropPPh 2 ) 2 ]BF 4 featuring two bidentate tropPPh 2 ligands (trop=5 H ‐dibenzo[ a,d ]cyclohepten‐5‐yl)). Besides Ru I , this ligand scaffold stabilizes ruthenium complexes in oxidation states ranging from Ru 0 to Ru II . No further reactivity with this complex has been reported to date.…”
Section: Figurementioning
confidence: 99%
“…Besides Ru I ,t his ligand scaffold stabilizes ruthenium complexes in oxidation states ranging from Ru 0 to Ru II . [5] No further reactivity with this complex has been reported to date.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Characterization of intermediates in chemical processes is of paramount importance to understand and improve their performance. In particular, isolation of paramagnetic complexes involved in single electron transfer (SET) redox events is an arduous task, especially for main group elements, due to their high reactivity . Bismuth redox catalysis has recently emerged as a versatile platform based on a single p-block element, for which both two- and one-electron (SET) redox cycles are within reach. , The latter represents a unique reactivity paradigm for a main group element, opening up unusual pathways for organic synthesis.…”
mentioning
confidence: 99%
“…Spectroscopic studies suggested that two diamagnetic hydrido–nickel complexes, 5 a and 6 a , participate in the catalytic cycle. Both complexes contain the diolefin‐amine trop 2 NH, which has remarkable properties as stabilizing ligand for low‐valent metal complexes . We could, therefore, isolate such low‐valent nickel hydrides and characterize them structurally.…”
Section: Resultsmentioning
confidence: 99%